The position function of a particle is given by
s=t^3−5t^2−8t, t≥0
where sis measured in meters and tin seconds. When does the particle reach a velocity of 15m/s?
so i got to v(s) = 3t^2-10t-815 =
start by looking at it as as difference of squares:
x^6 - y ^6 = (x^3 + y^3)*(x^3 - y^3)
then (x^3 - y^3) = (x-y)(x^2 + xy +y^2)
so...
(x-y)(x^2 + xy + y^2)(x^3 + y^3)
then look at x^3 + y^3 = (x+y)(x
A goldsmith mixed 10 grams of a 50% gold alloy with 40 grams of 15% gold alloy. What is the percent concentration of the resulting alloy?-50/100 x 10 = 5 GRAMS
15/100 x40 = 6 GRAMS
ADD = 11 GRAMS
1
We just started learning them in class and I have NO idea how to do them. Can someone PLEASE explain the basics and a simple example?
Thankss.-Say we have log10(100) this is just like saying 10 to wha
what equals to 5x + 2x + 5y + 2y
what equals to (5 + 2)x + (5 + 2)y
what equals to 7x + 7y-Not sure if im answering your question correctly??
step 1:This is the problem. We wont be able to get a numer
My daughter has the following math problem, and between 4 people (3 of us adults), we couldnt figure out how to solve it. Shes supposed to come up with the equation and the solution:
The Jaspers coll
(1)y=(9x^2-18x+18) e^x
(2)y=(3-x^2)(x^3-x+3)
(3) Find Dx(y)when y=9x-4/x-4(use positive exponent only)-Is that a direct copy from the book?
Please list the directions listed there too
Looks like you
for $200. According to the National Vital Statistics Report. 56(9), the probability that the female survives the year is 0.999544. Compute and interpret the expected value of this policy to the insura
1--A piece of rope 60 m long is cut into two pieces so that the longest piece is twice the length of the shorter. How long are the two pieces.
2--Mario is 18 years older than Joshua. If the sum of th
How do i completely factor this. Please help me out with this question. c;-you cant factor itit is already simplified-Is this really how the question is written in your book?????I think some info is m
fina all relative extreme ( max and min or neither )
y = -3x^5 + 5x^3
so what i did is :
y = -15x^4 + 15x^2
-15x^2 (x^2-1) = 0
x= 0 , x= 1 , x=-1
whats next ???-correct you got the value of x =
(hint: show that a+b>c)-This one is easiest to approach using proof by contradiction:suppose a + b
Now what to do with that?How about squaring both sides.You get
a^2 + 2ab + b^2 0.Therefore our su
5y- 3x + 2y + 8x
7y + 5x is the answer
could you please explain to me how to do this? :/-5y- 3x + 2y + 8x=......
5y + 2y = 7y, so -3x +8x = 5x.
You work in the order from left to right. Hope that h
Can someone show me calculus/algebra to prove that the derivative of f(x) =1/2 is f (x) =1/2 ?I know that is the answer but if I can I would like to be able to better explain why.-The derivative of f